The broken body: Israel, Christ and fragmentation - Coakley, Sarah (Challenges in contemporary theology, 2024)
"'Who, or why, or which or what is the Akond of SWAT?', wrote Edward Lear in one of his more elusive nonsense poems. No less elusive, however, is the somewhat parallel question: Who, or why, or which, or what, is the 'risen Jesus'? The opening chapter of this book will attempt to probe this misleadingly simple theological question afresh. In particular, it will propose a systematic solution to the task of analysing how historical, dogmatic, and what we might call 'spiritual', or 'ascetic', approaches to the quest for Jesus's identity might relate, and mutually inform one another. At the same time I shall begin to ask where the appropriately 'apophatic' dimensions of the task of Christology might also lie. The task is a curiously complicated one, as we shall see. Not only is there still great difficulty, even after two hundred years of 'historical Jesus research', in bringing modern historical/critical discussions about the identity of 'Jesus' into clear relation to the older credal, dogmatic reflection on his 'person'; but still less is there a consistent confidence manifested in contemporary systematic theology, as I see it, about the means and possibiity of a direct relation to the 'risen Jesus' now, about what this claim might mean, and about how the probative recognition of him might occur. Indeed, we might say that this last, pressingly existential, question has been all-but occluded - embarrassedly repressed, even - in the era of obsession about the 'historical' identity of Jesus"--